Pengaruh Iklan Islami Terhadap Minat Beli Calon Konsumen Matahari Dept. Store di Jawa Tengah - Saifudin, Saifudin (BISNIS, 2019)
The purpose of this research is to find out the influence of Islamic advertising (Islamic advertising messages, Islamic story illustrations and Muslim advertising stars) Mahatahari Dept. Store against the buying interest of prospective Mahatahari Dept. Store in Central Java. This research was conducted in Central Java Province with a sample size taken as many as 120 respondents with a purposive sampling method. Data was collected by distributing questionnaires using the Likert scale to measure 13 indicators. The analysis technique used is multiple linear regression analysis. The results of the study found that Islamic advertising messages, illustrations of Islamic stories and Muslim advertising stars had a positive and significant effect on consumers' buying interest. Based on the calculation of the coefficient of determination, it can be explained that the simultaneous influence of Islamic advertising message variables, illustrations of Islamic stories and Muslim advertising stars on consumer buying interest. While the partial results of the illustrative variable of Islamic stories and Muslim advertising stars have a positive and significant effect on consumer buying interest, but Islamic advertising message variables have no effect on buying interest.